Sex differences in functional and structural alterations of hippocampus region in chronic pain: a DTI and resting-state fMRI study - Zhou, Jun-Zhi; Deng, Jie; Luo, De-Xing; Mai, Jing-Wen; Wu, Jia-Yan; Duan, Yu-Juan; Dong, Bo; Xin, Wen-Jun; Xu, Ting; Wei, Jia-You (Frontiers in Neuroscience, 2024)
IntroductionIt is well known that there are significant differences in the prevalence of chronic pain between males and females. Human and animal imaging studies have shown that chronic pain profoundly alters the structure and function of brain regions. However, there is limited research on the sex-specific mechanisms underlying the brain plasticity and adaptive changes associated with chronic pain. In this article, we conducted a multimodal study to evaluate how nerve injury-induced chronic pain affects the brain.MethodsMale and female Sprague-Dawley (SD) rats with spared nerve injury (SNI) model underwent resting-state functional magnetic resonance imaging (rs-fMRI) (male sham group: n = 18; male SNI group: n = 18; female sham group: n = 20; female SNI group: n = 18) and magnetic resonance diffusion tensor imaging (DTI) (male sham group: n = 23; male SNI group: n = 21; female sham group: n = 20; female SNI group: n = 21) scanning. ICA method, Fractional amplitude of low-frequency fluctuations (fALFF), immunofluorescence staining, and graph theory analysis was utilized to extract the rs-fMRI changes of brain regions of each group.ResultsUsing SNI model, which promotes long-lasting mechanical allodynia, we found that neuropathic pain deeply modified the intrinsic organization of the brain functional network in male and female rats (main effect of operation: F = 298.449, P < 0.001). 64 independent components (ICs) in the brain were divided and assigned to 16 systems. In male rats, we observed significant alterations in the microstructure of the hippocampal cornu ammonis 1 and cornu ammonis 2 (CA1/CA2) region, as indicated by increased mean diffusivity (MD) (CA1_L: P = 0.02; CA1_R: P = 0.031; CA2_L: P = 0.035; CA2_R: P = 0.015) and radial diffusivity (RD) (CA1_L: P = 0.028; CA1_R: P = 0.033; CA2_L: P = 0.037; CA2_R: P = 0.038) values, along with enhanced activating transcription factor 3 (ATF3) expression. Conversely, in female rats, we found significant increases in the fractional amplitude of low frequency fluctuations (fALFF) value within the hippocampal dentate gyrus (DG) (F = 5.419, P = 0.023), accompanied by elevated c-Fos signal (F = 6.269, P = 0.031). Furthermore, graph theory analysis revealed notable differences in the small-world network of the hippocampal system in female rats, characterized by reduced small-world attributes and increased inter-nodal transmission efficiency.DiscussionOur study indicates sex differences in structural and functional alterations in the hippocampal system in rats under chronic pain conditions. The results suggest that the hippocampus system plays an important role in the different mechanisms of chronic pain in different sexes. These findings provide reliable insights to explore the complex mechanisms underlying sex differences in chronic pain.